High-Sensitivity Refractive Index Sensor Based on a Cascaded Core-Offset and Macrobending Single-Mode Fiber Interferometer - Teng, Chuanxin; Zhu, Yongjie; Yu, Fangda; Deng, Shijie; Yuan, Libo; Zheng, Jie; Cheng, Yu (Frontiers in Materials, 2021)
A high-sensitivity Mach–Zehnder interferometer (MZI) based on the cascaded core-offset and macrobending fiber structure is proposed for refractive index (RI) measurement. The core offset structure makes the fiber core mode couple to the cladding modes, and some of them recouple back to the fiber core at the macrobending structure forming a model interference effect. The liquid RI can be measured by monitoring the spectral shift of the modal interference. The RI sensing performances for the interferometers with different macrobending radii and core offsets are investigated experimentally. Experimental results show that when the core offset is 2 μm and the macrobending radius is 5.5 mm, the sensitivity can reach to 699.95 nm/RIU for the RI of 1.43. The temperature dependence for the proposed sensor is also tested, and a temperature sensitivity of 0.112 nm/°C is obtained.